Trust, investment and competition: theory and evidence from German car manufacturers - Giacomo Calzolari; Leonardo Felli; Johannes Koenen; Giancarlo Spagnolo; Konrad O. Stahl (Center for Economic Studies and ifo Institute (CESifo), 2019)
Based on data from a comprehensive benchmarking study on buyer-supplier relationships in the German automotive industry, we show that more trust in a relationship is associated with higher idiosyncratic investment by suppliers and better part quality - but also with more competition among suppliers. Both associations hold only for parts involving comparatively unsophisticated technology, and disappear for parts involving sophisticated technology. We rationalize all these observations by means of a relational contracting model of repeated procurement with non-contractible, buyer-specific investments. In relationships involving higher trust, buyers are able to induce higher investment and more intense competition among suppliers - but only when the buyer has the bargaining power. This ability disappears when the bargaining power resides with the supplier(s).
Keywords: D86; L14; L62; O34; 330; relational contracts; hold-up; buyer-supplier contracts; bargaining power